2003
DOI: 10.1038/sj.hdy.6800240
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific evolution of Canary Island Plecotine bats, based on mtDNA sequences

Abstract: Island differentiation and relationships with congenerics were investigated in the endemic Canary Island bat Plecotus teneriffae, based on B1 kb of mtDNA from the 16S rRNA and cytochrome b genes. P. teneriffae had closer affinities with P. austriacus than with P. auritus. Levels of differentiation between Canary Islands were quite high relative to Pipistrelle-like bats, consistent with philopatric behaviour in the Plecotus genus. Cladogenesis within P. teneriffae appears to have occurred after the emergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…, 2000a,b; Helfgott et al. , 2000; Pestano et al. , 2003), may not have been present until geologically recently.…”
Section: Historical Biogeography Of African Flora and Avifaunamentioning
confidence: 99%
“…, 2000a,b; Helfgott et al. , 2000; Pestano et al. , 2003), may not have been present until geologically recently.…”
Section: Historical Biogeography Of African Flora and Avifaunamentioning
confidence: 99%
“…Populations of mammals on nearby islands often have similar phylogeographical histories due to identical patterns of colonization or geomorphological factors (Trujillo et al. , 2002; Pestano et al. , 2003; Vogel et al.…”
Section: Introductionmentioning
confidence: 99%
“…The cyt-b sequence divergence between the single haplotype from the Canary Islands and the mainland lineages is relatively high (averaging 3.9 and 4.2% to Moroccan and the Iberian haplotypes respectively; Table 3) and corresponds to the value reported by Pestano et al (2003) for a Canarian population and one specimen from Iberia sequenced at the same gene. Pestano et al (2003), however, found two slightly divergent cyt-b haplotypes among seven barbastelles from Tenerife Island, while all our Canarian samples (including three from Tenerife and three from La Gomera) were identical.…”
Section: The Barbastelles Of the Canary Islandsmentioning
confidence: 96%
“…Pestano et al (2003), however, found two slightly divergent cyt-b haplotypes among seven barbastelles from Tenerife Island, while all our Canarian samples (including three from Tenerife and three from La Gomera) were identical. Our Canarian samples proved to be identical even when they where sequenced for the more rapidly evolving CR (Table 1).…”
Section: The Barbastelles Of the Canary Islandsmentioning
confidence: 98%